2019
DOI: 10.1016/j.rmed.2019.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Patient journey and treatment patterns in adults with IPF based on health care data in Sweden from 2001 to 2015

Abstract: Background: For patients with idiopathic pulmonary fibrosis (IPF), there is limited real-world data on patient journey and treatment patterns. Aim: To explore predictors of early diagnosis and treatment initiation, and treatment patterns in IPF patients using linked data from Swedish registers and electronic medical records (EMRs). Population: A national cohort (C1) of 17,247 pulmonary fibrosis patients (ICD-10 code J84.1; no competing diagnosis) diagnosed between 2001 and 2015, and an EMR-based regional subse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 39 publications
1
20
0
Order By: Relevance
“…Two recent studies of US Medicare and commercially-insured patients found that those who indexed on pirfenidone had higher adherence and longer persistence than patients who indexed on nintedanib; however, the mean follow-up time was less than half of that reported in this study and there are difference in the patient populations and patient selection criteria [ 25 , 26 ]. In an analysis of Swedish patients with IPF treated with pirfenidone, 24.7–41.8% (depending on data source) were persistent at 1 year compared with over 50% in our study; however, they used a 30-day gap to define discontinuation compared to the 60-day gap used in this study [ 27 ]. Treatment pattern analysis was not available on patients who indexed on nintedanib in the Swedish analysis due to low utilization during the study time frame.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Two recent studies of US Medicare and commercially-insured patients found that those who indexed on pirfenidone had higher adherence and longer persistence than patients who indexed on nintedanib; however, the mean follow-up time was less than half of that reported in this study and there are difference in the patient populations and patient selection criteria [ 25 , 26 ]. In an analysis of Swedish patients with IPF treated with pirfenidone, 24.7–41.8% (depending on data source) were persistent at 1 year compared with over 50% in our study; however, they used a 30-day gap to define discontinuation compared to the 60-day gap used in this study [ 27 ]. Treatment pattern analysis was not available on patients who indexed on nintedanib in the Swedish analysis due to low utilization during the study time frame.…”
Section: Discussionmentioning
confidence: 83%
“…Among the subset of patients with 12 months of follow-up data, all-cause and respiratoryrelated adjusted annual costs were similar regardless of To account for titration, an additional 7 days were added to the day supply of the first pirfenidone prescription claim, unless the supply was 207 pills for 30 days, which is correct if following the recommended titration schedule 3 Patients with a lung transplant before the end of a gap of ≥60 days were not considered to have discontinued 4 Among those with a lung transplant 5 Among those who discontinued treatment index medication; however, index drug-related costs were lower for patients who indexed on pirfenidone. Adherence to and persistence with antifibrotic therapies in IPF are important for maintaining treatment benefits and slowing lung function decline; however, there is limited existing data on treatment patterns as pirfenidone and nintedanib have only been recently approved to treat IPF in the US [25][26][27]. Two recent studies of US Medicare and commercially-insured patients found that those who indexed on pirfenidone had higher adherence and longer persistence than patients who indexed on nintedanib; however, the mean follow-up time was less than half of that reported in this study and there are difference in the patient populations and patient selection criteria [25,26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In real-world clinical practice, the rates of pirfenidone discontinuation owing to any reason and owing to ADEs at 12 months have been reported to be 35-75% (Ogura et al, 2015;Bando et al, 2016;Barratt et al, 2018;Ogawa et al, 2018;Uehara et al, 2018;Sköld et al, 2019) and 15-35% (Ogura et al, 2015;Bando et al, 2016;Galli et al, 2017;Barratt et al, 2018), respectively. In our study, the rates of pirfenidone discontinuation owing to any reason and owing to ADEs at 12 months were 51.7 vs. 33.3% and 35.0 vs. 33.3% in the conventional vs. collaborative management groups; these values were generally within the range reported previously.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Cough, dyspnea, and fatigue are frequently underrecognized in primary care, leading to delays in referral. 51,52 The use of generic PROMs and PREMs in primary care may bring dyspnea and cough to light, raising the suspicion and early detection of the disease.…”
Section: Early and Accurate Diagnosis With Patient-centered Educationmentioning
confidence: 99%